Replication Data for: The myth of the De Geer Zone: a change of paradigm for the opening of the Fram Strait - Koehl, Jean-Baptiste P. (DataverseNO, 2023)
Supplements and high-resolution version of the figures and supplements in the following manuscript: "The myth of the De Geer Zone: a change of paradigm for the opening of the Fram Strait". High-resolution versions of the figures are necessary to identify individual structures presented and discussed in the text.